Manage to win : revitalize your business, wrong-foot your competitors - Paley, Norton (Thorogood, 2005)
Learn how to reshape and reposition your company to meet tougher challenges and competitors, when to confront and when to retreat, how to assess risk and opportunity and how to move to seize opportunities and knock-out the competition.